TINDAK PIDANA PENCURIAN JENAZAH DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Nur Vika Arisfianti; Dara Puspitasari; Dwi Wachidiyah Ningsih (Judge : Jurnal Hukum, 2026)
The protection of human dignity does not end with death, but continues through the legal safeguarding of a deceased person’s body. In Indonesiian society, a corpse holds a sacred position grounded in moral, religious, and cultural values, which requires respectful treatment and legal protection. However, in practice, acts involving the taking or theft of corpses still occur and constitute serious violations of legal norms as well as humanitarian values. Such acts not only disturb public order but also undermine respect for human dignity. Accordingly, criminal law assumes a pivotal role in governing and preventing unlawful conduct directed against corpses. This research examines the criminalization of corpse theft under Indonesiian criminal law, with a specific focus on the regulatory framework established by the newly promulgated Indonesiian Criminal Code. The research focuses on examining the legal construction, elements of the offense, and the legal rationale underlying the criminalization of acts involving the unlawful taking of a corpse. This research employs a normative juridical approach by incorporating both statutory and conceptual frameworks. The legal materials used consist of primary sources in the form of legislative provisions, secondary sources including legal literature and academic journals, as well as tertiary sources serving as supplementary references. The results of this research show that the legal framework governing corpses theft within Indonesiian criminal law embodies the state’s dedication to safeguarding human dignity and affirming humanitarian principles. Nevertheless, challenges remain in terms of legal interpretation and consistent application by law enforcement authorities. Therefore, a comprehensive and value-oriented understanding of the relevant criminal provisions is essential to guarantee legal certainty, promote justice, and provide effective legal protection for human remains within the Indonesiian legal system.